Wilson Disease-Induced Acute Liver Failure (NWI = 13) Salvaged without Liver Transplant by Plasmapheresis - Mirza, Nida; Bharadwaj, Ravi; Malhotra, Smita; Sibal, Anupam (Journal of Child Science, 2021)
Wilson disease (WD) is a disorder of copper metabolism resulting in accumulation of copper in vital organs of the human body, predominantly in the liver and the brain. Acute liver failure in WD has a bad prognosis, especially with a score ≥11 in the revised WD prognostic index; emergency liver transplantation is considered the only life-saving option in this scenario. Here, we reported a girl patient with WD-induced liver failure and poor prognostic score who was rescued by plasmapheresis. She also manifested severe Coombs negative hemolytic anemia and acute kidney injury. This case report highlights the utility of an adjunctive modality besides liver transplantation for the management of fulminant liver failure caused by WD.
Keywords: acute liver failure; Wilson disease; plasmapheresis